2021
DOI: 10.3390/cryst12010043
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thiourea Containing Composite Additives on Nickel Electrodeposition in Ammoniacal Solution

Abstract: Composite additives have an important influence on the process of metal electrodeposition and the quality of a metal deposited layer. In this work, the additive thiourea (TU) was compounded with cetyltrimethyl ammonium chloride (CTAC), sodium dodecyl sulfate (SDS) and polyethylene glycol 20,000 (PEG20000), and their effect on the cyclic voltammetric behavior, electrochemical nucleation mechanism, crystallographic orientations and surface morphology of the nickel electrodeposition in ammoniacal solution were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…At an SDS concentration of 0.04 g/L, the anodic current efficiency reached its ACCEPTED MANUSCRIPT maximum at 71.97%, and the anodic energy consumption decreased to its minimum at 3375.99 kW h t -1 . Analysis indicated that the addition of SDS as an auxiliary additive forms a passivation film on the electrode surface, reducing by-product generation, hindering the dissolution of electrode materials, and enhancing the electrochemical stability of Mn electrolysis 30 . At lower SDS concentrations, the activation energy of crystal faces is reduced, facilitating nucleation, thus increasing current efficiency and reducing energy consumption 29 .…”
Section: Effect Of Na2so3 and H2seo3 Composite On The Electrolytic Re...mentioning
confidence: 99%
“…At an SDS concentration of 0.04 g/L, the anodic current efficiency reached its ACCEPTED MANUSCRIPT maximum at 71.97%, and the anodic energy consumption decreased to its minimum at 3375.99 kW h t -1 . Analysis indicated that the addition of SDS as an auxiliary additive forms a passivation film on the electrode surface, reducing by-product generation, hindering the dissolution of electrode materials, and enhancing the electrochemical stability of Mn electrolysis 30 . At lower SDS concentrations, the activation energy of crystal faces is reduced, facilitating nucleation, thus increasing current efficiency and reducing energy consumption 29 .…”
Section: Effect Of Na2so3 and H2seo3 Composite On The Electrolytic Re...mentioning
confidence: 99%